Rekonstruksi Teologis terhadap Pendekatan Pembelajaran Konstruktivisme Sosial [Theological Reconstruction Toward Social Constructivism Learning Approach] - Andi Krisdianto Nugroho (Diligentia: Journal of Theology and Christian Education, 2020)
The main questions on this essay is how to integrate Christian faith in social constructivism or how do we relate both and on the practical aspect, could Christian schools use constructivism? This paper approaches the problem by analyse the presuppositions of social constructivism to find out what are the main beliefs behind the view. Afterwards, the presuppositions of this theory are reviewed in the light of Biblical Christian doctrines because as believers should see through the Biblical worldview of the sound teaching. In conclusion, social constructivism can be used in Christian schools but with some cautionary notes. Students need to be educated that there is absolute truth, God is real, and the meaning of human life is not determined by the social community but is determined by God